Kinetic analysis of unilateral landings in female volleyball players after a dynamic and combined dynamic-static warm-up - Avedesian, J. M.; Judge, L. W.; Wang, H.; Dickin, D. C. (The Journal of Strength and Conditioning Research, 2019)
A warm-up is an important period before training or competition to prepare an athlete for the physical demands of subsequent activity. Previous research has extensively focused on the effects of warm-up in relation to various jumping performance attributes; however, limited research has examined the biomechanical nature of landings after common warm-up practices. Twelve female, collegiate-level volleyball players performed unilateral landings on the dominant and nondominant limb before and after dynamic warm-ups and combined dynamic-static (CDS) warm-ups. Kinetic variables of interest were measured at the hip and knee during the landing phase of a volleyball-simulated jump-landing maneuver. A significant 3-way interaction (warm-up × limb × time) for peak internal knee adduction moment was observed, as this kinetic parameter significantly increased (p = 0.01; d = 0.79) in the nondominant limb at 1-minute post-CDS warm-up. No other warm-up differences were detected; however, significant main effects of limb were determined for dominant-limb internal hip abduction moment (p < 0.01; d = 1.32), dominant-knee internal rotation moment (p < 0.01; d = 1.88), and nondominant-knee external rotation moment (p < 0.01; d = 1.86), which may be due to altered hip and trunk mechanics during the jump landings. This information provides strength and conditioning professionals with biomechanical information to determine warm-up protocols that reduce the risk of injury in female volleyball athletes.